2019
DOI: 10.1111/famp.12479
|View full text |Cite
|
Sign up to set email alerts
|

Resilience Factors and Suicide Risk for a Sample of Transgender Clients

Abstract: This study explored how individual‐ and community‐based resilience factors operated together in order to reduce risk of suicide for a sample of transgender therapy clients. We collected cross‐sectional survey data from 106 transgender therapy clients at a local community center, including demographic information, experiences of relational support, participants' emotional stability, and risk for suicide. Results from our mediation analysis indicated that high levels of perceived relational support are related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 55 publications
0
5
0
3
Order By: Relevance
“…The BAMS module did not include any elements targeted at enhancing resilience. This is a promising goal for future development of interventions adapted to TNG populations, given the findings from this study and studies indicating the importance of resilience in this group (Edwards, Torres Bernal, Hanley, & Martin, 2019; Singh, Hays, & Watson, 2011). Though there were no statistically significant differences between groups, these results suggest the need for a larger trial to explore how minority stress interventions uniquely contribute to change in proximal and distal stressors for transgender clients.…”
Section: Discussionmentioning
confidence: 89%
“…The BAMS module did not include any elements targeted at enhancing resilience. This is a promising goal for future development of interventions adapted to TNG populations, given the findings from this study and studies indicating the importance of resilience in this group (Edwards, Torres Bernal, Hanley, & Martin, 2019; Singh, Hays, & Watson, 2011). Though there were no statistically significant differences between groups, these results suggest the need for a larger trial to explore how minority stress interventions uniquely contribute to change in proximal and distal stressors for transgender clients.…”
Section: Discussionmentioning
confidence: 89%
“…Alguns dados estatísticos corroboram com os resultados encontrados. Uma pesquisa realizada nos Estados Unidos acerca da discriminação relacionada a pessoas trans identificou que 63 % dos entrevistados relataram ter sofrido discriminação, maus tratos, abandono, perda de emprego, negação de atendimento em serviços de saúde, violência física e sexual (Edwards et al, 2019). No Brasil, de acordo com dados da ANTRA, em 2020 houve um aumento de 49 % do número de assassinatos de pessoas trans quando comparado ao ano de 2019.…”
Section: Discussionunclassified
“…Tucker et al (2018) em seu estudo demonstra que a vida da população trans está constantemente em vulnerabilidade, visto que o risco de tentativa de suicídio nessa população é vinte vezes maior do que em pessoas cisgêneras. Os aspectos supracitados são de fundamental importância, pois, o apoio social, estabilidade emocional e a presença de políticas anti discriminação podem configurar resposta à alta taxa de mortalidade dessa população (Budhwani et al, 2018;Edwards et al, 2019;Tebbe & Moradi, 2016) A classe 2 e a classe 5, diretamente interligadas, denominadas de "Visibilidade trans" e "Riscos à saúde trans", discutem alguns fatores que podem proporcionar uma vida equiparável para com a vivência trans. Desse modo, é preciso que haja interferência de poderes sociais na luta à vida dessa população.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…These forms of resilience have real-world impacts, especially on the health and wellbeing of TGD individuals. For example, relational support for TGD individuals is related to emotional stability, which in turn is correlated with lowered risk of suicidality [38]. Pollit and colleagues [37] also found that being affirmed and having inclusive adults reduces mental health risk factors to the level of the general youth population.…”
Section: Tgd Youth Resiliencementioning
confidence: 99%